Microsatellite instability in breast carcinoma - Smolarz, Beata; Romanowicz-Makowska, Hanna; Kozłowska, Elżbieta; Zadrożny, Marek; Stetkiewicz, Tomasz; Pertyński, Tomasz; Kulig, Andrzej (Menopause Review/Przegląd Menopauzalny, 2004)
Background: Microsatellite instability (MSI) is due to defective DNA mismatch repair. Defects in DNA mismatch-repair (MMR) genes lead to replication errors revealed as instability in microsatellite markers. Studies have shown that both hereditary breast cancer and sporadic breast cancer may be associated with mutations in a mismatch repair genes, such as MSH2, MLH1, PMS1, PMS2 and MSH6. Approach: Results from studies that assayed microsatellite instability in hereditary and sporadic breast cancer are reviewed. Conlusion: Several data suggest that microsatellite instability seem to be a risk factor both breast cancer in subjects belonged to HNPCC (Hereditary Nonpyloposis Colorectal Cancer) families with high incidence of this cancer and sporadic breast cancer.